PNPLA3 gene variation modulates diet-induced improvement in liver lipid content in type 2 diabetes - Pafili, Kalliopi; Zaharia, Oana-Patricia; Strassburger, Klaus; Knebel, Birgit; Herder, Christian; Huttasch, Maximilian; Karusheva, Yanislava; Kabisch, Stefan; Strom, Alexander; Nowotny, Bettina; Szendrödi, Julia; Roden, Michael (Clinical nutrition, 2025)
BACKGROUND&AIMS: Lifestyle-induced weight reduction remains crucial for managing type 2 diabetes and steatotic liver disease, but its effectiveness varies. We postulated that the G allele in the rs738409 single nucleotide polymorphism within patatin-like phospholipase domain-containing protein 3 (PNPLA3), which associates with metabolic dysfunction-associated steatotic liver disease, also modulates diet-related metabolic effects. - METHODS: Participants with type 2 diabetes were randomized to 8-week hypocaloric diets (energy intake: -1,256 kJ/d of, <30 kcal% fat): high in cereal fiber and coffee excluding red meat (HF-RM + C; n = 16), or low in cereal fiber, devoid of coffee, but high in red meat (LF + RM-C; n = 15). Whole-body insulin sensitivity (M value) was assessed using [2H]glucose and hyperinsulinemic-normoglycemic clamps, hepatic lipid content (HCL) and body fat volumes by magnetic resonance spectroscopy/imaging before and after intervention. - RESULTS: Despite comparable weight loss, HCL decreased more in non-carriers (-65 %) than in G-allele carriers (-36 %) upon HF-RM + C diet (both p < 0.05 vs baseline and between groups), but only among non-carriers (-46 %, p < 0.05 vs baseline) upon LF + RM-C. Upon HF-RM + C diet, increase in insulin sensitivity was not different between carriers (+27 % p = 0.051 from baseline) and non-carriers (+21 %, p = 0.032 from baseline), p > 0.05 for between-group comparison. Upon LF + RM-C diet, both groups equally improved their whole-body insulin sensitivity (+42 % for non-carriers and +37 % for carriers, p < 0.05 vs baseline). Upon HF-RM + C diet, non-carriers decreased circulating interleukin-18 from baseline by -31 %, whereas, upon LF + RM-C diet, non-carriers decreased circulating anti-inflammatory interleukin-1 receptor antagonist levels by 14 % (both p < 0.05 vs baseline). - CONCLUSIONS: Humans with the PNPLA3 G-allele show modified dietary-induced effects on steatotic liver disease in type 2 diabetes despite body weight reduction. Registration at Clinicaltrials.gov, Identifier number: NCT01409330.
Gesehen am 12.01.2026